1991
DOI: 10.3109/08941939109140763
|View full text |Cite
|
Sign up to set email alerts
|

Improved Xenograft Survival with Continuous Infusion Deoxyspergualin and RATG

Abstract: The critical shortage of available donor organs is the major limit to current allogeneic transplantation. Xenografting has the potential to overcome this difficult problem. Suppressing the vigorous rejection response remains a major obstacle to the clinical application of xenografting, 15-Deoxyspergualin (DOSP), a potent new immunosuppressive agent has been shown to be effective in allogeneic and xenogeneic experimental models. This study tests DOSP in combination with rabbit antithymocyte globulin (RATG) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…In accordance with Rosengard et al (1986) we concluded that the type of rejection was primarily of the humoral type (12,16,21). This has also been proposed by others using different treat-ment schedules for prevention of xenograft rejection (5,8,14). In other concordant models, however, an accelerated type of first-set rejection, or a combined humoral and cellular rejection, has been described (6,9,10,11,13,15).…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with Rosengard et al (1986) we concluded that the type of rejection was primarily of the humoral type (12,16,21). This has also been proposed by others using different treat-ment schedules for prevention of xenograft rejection (5,8,14). In other concordant models, however, an accelerated type of first-set rejection, or a combined humoral and cellular rejection, has been described (6,9,10,11,13,15).…”
Section: Discussionsupporting
confidence: 88%
“…In these studies, deoxyspergualin administered at 2-5 mg/kg has proven to be as efficacious or better than ciclosporin A and FK506 [9], while combinations of deoxyspergualin with ciclosporin A and/or steroids have provided addi tional benefit [10], In models of xenotransplantation, monotherapy with deoxyspergualin has produced mixed results; however, it has been shown to markedly enhance the suppressive ability of other monotherapies [11][12][13][14]. A second very important feature of the deoxyspergualin action is its ability to reverse established acute rejection [15].…”
Section: Experimental Transplantationmentioning
confidence: 99%